A implementação da reforma do Novo Ensino Médio na rede pública estadual de São Paulo: desvendando as intenções - Azevedo, Raquel Tegedor (2024)
This master's thesis presents an investigation into the implications for teaching after the reform of secondary education implemented in the São Paulo state public school system, focusing on the Curricular Enrichment offered in 2022 and 2023, as well as the concept of education offered to young students. The analysis is made through the lens of the first generation of critical theory represented by Theodor W. Adorno, Max Horkheimer and Herbert Marcuse, in order to explore the consequences for the work of teachers qualified to teach Portuguese language curricular components. For this purpose, were selected and analyzed the contents of the prescribed curriculum effective until 2020 and the curriculum used from 2021, more specifically the curricular enrichments of the formative pathways, implemented in 2022 and 2023. The following stages of analysis were used to achieve the research proposal: 1. study of the curricular matrices; 2. mapping of the curricular enrichment that include the allocation of classes to Portuguese language teachers; 3. analysis of the syllabuses of the curricular enrichment; 4. examination of the contents and objects of knowledge proposed in the didactic sequences set out in the Support Material for Curricular Enhancement and 5. final comparison of the data obtained. It was found that this stage of basic education at the reduction in the workload of the curricular components of Basic General Training and the proposed curricular organization for Curricular Deepening have been used to adapt individuals to the interests of the administered Society. Thus, the New Secondary Education in São Paulo has guaranteed an increase in teaching work, since the content proposed in the Curricular Enrichment does not always converge with that acquired in their initial training, as well as the fact that the proposed training model contributes to the pseudo-training of students and the consequent devaluation of teachers